Application and Future Development of Big Data Technology in Intelligent Transportation Systems - Yang, Yuhe (International Journal of Computer Science and Information Technology, 2024)
In this research plan, we employ a literature review approach to summarize the current state and development trends of big data technology in intelligent transportation systems. By collecting and analyzing relevant literature from both domestic and international sources, we organize case studies of big data applications in intelligent transportation systems. This allows us to analyze the shortcomings of existing research and identify the challenges that will be faced in future development. Additionally, we can propose future research directions and key focuses. Through this research, we hope to provide valuable assistance for future studies in this field.